No Reason to Worry About German Mortgages? An Analysis of Macroeconomic and Individual Drivers of Credit Risk - Nataliya Barasinska; Philipp Haenle; Anne Koban; Alexander Schmidt (Journal of Financial Services Research, 2023)
This paper analyzes the macroeconomic and borrower-specific credit risk factors of residential real estate mortgages in Germany. Relying on a macroeconomic panel VAR model, we show a significant link between foreclosures, house price dynamics and unemployment. Using microeconomic regressions, we show that defaults are driven mostly by income and liquidity rather than loan-to-value (LTV) ratios. Based on those insights, we calibrate a structural model which predicts a significant increase in mortgage losses in a stress scenario, driven only partially by high-LTV loans. Hence, from a macroprudential perspective our findings support the need for a broad toolkit going beyond LTV-limits.
Keywords: G01; G17; G21; G28; 330; Residential real estate; Mortgages; Credit risk; Stress testing; Germany